Peer victimization and its impact on adolescent brain development and psychopathology - Quinlan, Erin Burke; Barker, Edward D.; Luo, Qiang; Banaschewski, Tobias; Bokde, Arun L. W.; Bromberg, Uli; Büchel, Christian; Desrivières, Sylvane; Flor, Herta; Frouin, Vincent; Garavan, Hugh; Chaarani, Bader; et al. (Molecular psychiatry, 2020)
Chronic peer victimization has long-term impacts on mental health; however, the biological mediators of this adverse relationship are unknown. We sought to determine whether adolescent brain development is involved in mediating the effect of peer victimization on psychopathology. We included participants (n = 682) from the longitudinal IMAGEN study with both peer victimization and neuroimaging data. Latent profile analysis identified groups of adolescents with different experiential patterns of victimization. We then associated the victimization trajectories and brain volume changes with depression, generalized anxiety, and hyperactivity symptoms at age 19. Repeated measures ANOVA revealed time-by-victimization interactions on left putamen volume (F = 4.38, p = 0.037). Changes in left putamen volume were negatively associated with generalized anxiety (t = −2.32, p = 0.020). Notably, peer victimization was indirectly associated with generalized anxiety via decreases in putamen volume (95% CI = 0.004-0.109). This was also true for the left caudate (95% CI = 0.002-0.099). These data suggest that the experience of chronic peer victimization during adolescence might induce psychopathology-relevant deviations from normative brain development. Early peer victimization interventions could prevent such pathological changes.
Gesehen am 29.05.2024